THE ROLE OF TRIBULUS TERRESTRIS ON MALE INFERTILITY BASED ON CLINICAL TRIALS PERSPECTIVE: A NARRATIVE REVIEW - Dona, Suzana; Kintoko, Kintoko; Mochammad Saiful, Bachri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
Tribulus terrestris is a widely recognized herb with potential applications in healthcare. Male factor infertility, often stemming from testicular disorders, is frequently linked to inadequate sperm quantity and quality. While botanical products, including herbal medicines, have shown both positive and negative effects on male fertility and testicular function in the literature, this narrative review specifically aimed to identify clinical trials investigating the potential benefits of Tribulus terrestris in reducing male infertility and enhancing semen and hormonal parameters. A literature review methodology was employed, utilizing Scopus, PubMed, and Cochrane databases to gather full-text accessible published works from 2013 to 2022. Initially, 28 studies were identified; 24 were excluded, leaving three for full-text evaluation. Ultimately, three articles met the inclusion criteria and were included in this review. Based on the reviewed articles, Tribulus terrestris extract appears to influence the quantity and quality of spermatozoa, as well as reproductive hormone levels. Two articles reported a significant increase in sperm parameters and hormone levels. However, one article indicated no meaningful correlation between Tribulus terrestris use and an increase in testosterone levels. Further data are needed to definitively determine the efficacy of Tribulus terrestris as an infertility treatment.